Nutrition related practices of mothers of under-five children - Haldar, Pratiti; Viswanath , Lekha; Srivastava , Ashok Kumar (Indian Journal of Community Health, 2024)
Background: Childhood nutrition; a term which rings the bell in everyone’s mind especially the mothers of a child. Good nutrition for a child is a fact that cannot be denied for a healthier growth of a child. Individual families or communities have their own practices and belief and their own choices regarding their dietary practices. Aims & Objectives: The objectives of the study were to assess the nutritional knowledge of mothers of under-five children, assess the nutrition related practices of mothers of under-five children and develop multicomponent program for mothers of malnourished children. Methods & Material: An exploratory survey was carried out among 146 mothers of malnourished children. The instruments used were socio-demographic profile, knowledge questionnaire on Nutrition of children and structured questionnaire on Nutrition related practices of mothers. Results: The results revealed that 129 (88.3%) mothers had average knowledge. About 71 (48.6%) mothers had moderately adequate practices and 51 (35%) had inadequate practices regarding nutrition for children. Conclusion: Mothers knowledge and dietary practices they adopt for their child has an invariable effect on their nutritional status.